Analisis User Interface dan User Experience Kamus Besar Bahasa Indonesia (KBBI) Digital - Pratama, Pandu Meidian; Putikadyanto, Agus Purnomo Ahmad (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
In the digital era and increasingly developing technology, digital dictionaries, such as the Big Indonesian Dictionary (KBBI), have become an inseparable part of our daily lives. User experience and user interface in digital KBBI are very important factors in ensuring its effectiveness and usability. The method used in this research is simple qualitative and quantitative descriptive methods. Descriptive methods are needed to describe the data obtained from the KBBI user survey and quantitative data is used to provide a percentage of the KBBI user survey. This research analyzes qualitative and quantitative data from users of the Big Indonesian Dictionary (KBBI) using survey filling procedures. A total of 100 students filled out this survey and data was obtained for 90 students using KBBI. Of the 90 students, 96% of them are digital KBBI users. In terms of user interface, digital KBBI users expressed satisfaction by showing an NPS score of +5 and user experience showing the number 0 on the NPS scale. However, users realize that the digital KBBI needs improvement in the future so that it can be used by all groups and has a better appearance.